Antioxidant and molecular response of mutant and native rice (Oryza sativa L.) varieties grown under salt stress - Arvas, Yunus Emre; Kocacaliskan, Ismail; Erisen, Semiha; Ordu, Emel (SPRINGER, 2023)
This study was carried out in a tissue culture medium using two salt stress-tolerant varieties (Oryza sativa L. cv. Dhan47 and Kiziltan mutant8) and two stress resistance varieties (Oryza sativa L. cv. Maras Yellow Rice and Kiziltan) at 50 mM, 100 mM and 200 mM NaCl concentrations in two different periods (fifteen and thirty days). In this study, we analysed root and stem length, antioxidant enzyme activities and gene expressions. Among the varieties, the highest size was observed in the maras variety, and the least length was observed in the dhan47 rice varieties in the 30-day stem length results. While there was no adverse effect on root lengths as much as 100 mm, it was observed that it had a negative impact on a 200 mM medium. In the 30-day results, it was observed that the SOD activity in the leaves of the Kiziltan variety decreased compared to the control, while it was observed that the activity increased up to 100 mM salt concentration in the roots. It was determined that CAT activity increased in leaves and roots at all concentrations compared to the control at increasing salt concentrations over a 15-day period. At the same time, it was observed that CAT activity was the highest at 100 mM salt concentration on the leaves of dhan 47 plant. In the 30-day results, it was observed that FDH activity increased in leaves and roots in all rice varieties compared to the control. In gene expression analyses, the highest (7 times) gene expression in roots was observed on Kiziltan100 mM salt concentration. The highest relative expression (14 times) in leaves was on the Kiziltan mutant leaf at 200 mM salt concentration. The results showed different responses in physiological effects, antioxidant activities and gene expression analyses as salt concentrations of all rice varieties. With the results obtained in this study, it is expected that different rice varieties that are sensitive and resistant to salt stress will contribute to the usability of agricultural lands where salinity is gradually increasing.
Keywords: Salinity; Proline; Superoxide dismutase; Formate dehydrogenase; Methionine sulfoxide reductase; OXIDATIVE STRESS; GENE-EXPRESSION; ENZYME-ACTIVITIES; TOLERANCE; MECHANISMS; FAMILY; Life Sciences & Biomedicine - Other Topics